2006
DOI: 10.1016/j.bbabio.2006.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as antioxidant, geroprotector and anticarcinogen

Abstract: The effect of the pineal indole hormone melatonin on the life span of mice, rats and fruit flies has been studied using various approaches. It has been observed that in female CBA, SHR, SAM and transgenic HER-2/neu mice long-term administration of melatonin was followed by an increase in the mean life span. In rats, melatonin treatment increased survival of male and female rats. In D. melanogaster, supplementation of melatonin to nutrient medium during developmental stages produced contradictory results, but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
152
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(168 citation statements)
references
References 152 publications
6
152
1
5
Order By: Relevance
“…8 In our experiments the treatment of transplantable HER2 mammary carcinoma and Ehrlich carcinoma with metformin with potent scavenger of ROS melatonin, 12,58 effectively inhibited the tumor growth. It was shown that melatonin suppressed expression HER2 in mammary adenocarcinomas in transgenic HER2/neu mice.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In our experiments the treatment of transplantable HER2 mammary carcinoma and Ehrlich carcinoma with metformin with potent scavenger of ROS melatonin, 12,58 effectively inhibited the tumor growth. It was shown that melatonin suppressed expression HER2 in mammary adenocarcinomas in transgenic HER2/neu mice.…”
Section: Animalsmentioning
confidence: 99%
“…9 Treatment with melatonin inhibits development of mammary tumors in a number of another models both in vitro and in vivo. [10][11][12] In this paper, we for the first time present the results of study of effect of combined treatment with metformin and melatonin on some aging related biological parameters, on the survival and Population studies have shown that treatment with the antidiabetic biguanide metformin significantly reduced cancer risk. In our animal studies, metformin delayed the onset of mammary adenocarcinoma (MAC) in transgenic HeR-2/neu mice but not the onset of spontaneous mammary tumors in female SHR mice.…”
Section: Introductionmentioning
confidence: 99%
“…42 Melatonin significantly influences gonadotrophin and sexual function in animals 43 and may possibly play a role during puberty (eg, hypogonadism in children with melatonin hypersecretion due to a pineal tumor), 44 although little is otherwise known. 45,46 Other properties of melatonin include a mild reduction in blood pressure, 47,48 and antioxidative 12,49,50 and anti-inflammatory 51,52 effects; the latter two are considered to influence cancer growth and life span, 53,54 and have a beneficial effect in several pathological conditions. 55 The absence of melatonin secretion is not a life-threatening state, in contrast with some other hormonal deficiencies.…”
Section: Functions Of Melatoninmentioning
confidence: 99%
“…It controls many function in our daily life's especially sleepwake process, circadian rhythms. Melatonin is an excellent antioxidant, protective against many types of cancer (Anisimov et al 2006) and also contributes in communication of time of day to the infants through breast feed milk (Illnerova et al 1993). Melatonin has been used successfully for the treatment of jet-lag effects and other sleep disorder (James et al 1990;Jan and Espezel 1995).…”
Section: Introductionmentioning
confidence: 99%